2008
DOI: 10.1007/s11998-008-9148-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of self-stratifying compositions

Abstract: Paint applied as a single layer, and its spontaneous separation to form a primer and a top coat, is one of the newest concepts of the effective and economical application of two layers in one step. The influence of the molecular weight of epoxy oligomer and acrylic polymer and their ratio on self-stratification was investigated. The degree of stratification depending on molecular weight and their mutual ratio was determined using ATR-FTIR spectroscopy, differential scanning calorimetry, microscopy techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The surface energy difference between the two resins was considered to be an important factor in assessing whether stratication would occur, 10 the epoxy resin whose free surface energy was higher than that of polyacrylate began to move towards the substrate, and the polyacrylate moved towards the air interface. 10,[39][40][41] There existed an interface between the two parts in Fig. 4b and c, considered as the mixture of epoxy resin and the polyacrylate, it can be explained that this interface was formed by the aggregation of epoxy resin and the polyacrylate, the inner shell of the three-layer "core-shell" emulsions.…”
Section: Sem Analysismentioning
confidence: 99%
“…The surface energy difference between the two resins was considered to be an important factor in assessing whether stratication would occur, 10 the epoxy resin whose free surface energy was higher than that of polyacrylate began to move towards the substrate, and the polyacrylate moved towards the air interface. 10,[39][40][41] There existed an interface between the two parts in Fig. 4b and c, considered as the mixture of epoxy resin and the polyacrylate, it can be explained that this interface was formed by the aggregation of epoxy resin and the polyacrylate, the inner shell of the three-layer "core-shell" emulsions.…”
Section: Sem Analysismentioning
confidence: 99%
“…More precisely, Vink et al who studied a range of parameters which can influence the stratification process (curing agent, particle size, solvent evaporation, solubility …) finally concluded that the surface tension of the resins has a decisive role in the formation of two distinct layers [22]. Additionally, in 2009, Kuczynska et al demonstrated that, in their epoxy/acrylic formulations, the surface energy and in particular the polarity of acrylic resins are the most critical parameters for self-stratification to occur [28].…”
Section: Influence Of the Surface Energymentioning
confidence: 99%
“…The epoxy resins obtained were dissolved in a mixture of solvents: xylene/methyl isobutyl ketone/1-methoxy-2-propanol at a weight ratio of 50:30:20. 26 A stoichiometric amount of hardener was added to 50% solutions of the above. Jeffamine D-230 or Epikure 3115-X-70 was used as hardeners.…”
Section: Preparation Of Organic Coatings Based On the Obtained Epoxy mentioning
confidence: 99%